New Approach to the Surveillance of Pediatric Infectious Diseases From Ambulatory Pediatricians in the Digital Era. Issue 7 (July 2021) - Cohen, Robert; Béchet, Stéphane; Gelbert, Nathalie; Frandji, Bruno; Vie Le Sage, François; Thiebault, Georges; Kochert, Fabienne; Cahn-Sellem, Fabienne; Werner, Andreas; Ouldali, Naim; Levy, Corinne
Abstract : Background: Many ambulatory networks in several countries have established syndromic surveillance systems to detect outbreaks of different illnesses. Here, we describe a new Pediatric and Ambulatory Research in Infectious diseases network that combined automated data extraction from the computers of primary care pediatricians. Methods: Pediatricians who used the same software, AxiSanté 5-Infansoft for electronic medical records were specially trained in infectious diseases, encouraged to comply with French treatments' recommendations, use of point-of-care tests and vaccination guidelines. Infectious disease diagnoses in children <16 years old in the records triggered automatic data extraction of complete records. A quality control process and external validation were developed. Results: From September 2017 to February 2020, 107 pediatricians enrolled 57, 806 children (mean age 2.9 ± 2.6 years at diagnosis) with at least one infectious disease diagnosis among those followed by the network. Among the 118, 193 diagnoses, the most frequent were acute otitis media (n = 44, 924, 38.0%), tonsillopharyngitis (n = 13, 334, 11.3%), gastroenteritis (n = 12, 367, 10.5%), influenza (n = 11, 062, 9.4%), bronchiolitis (n = 10, 531, 8.9%), enteroviral infections (n = 8474, 7.2%) and chickenpox (n = 6857, 5.8%). A rapid diagnostic test was performed in 84.7% of cases of tonsillopharyngitis and was positive in 44%. The antibiotic recommendations from French guidelines were strictly followed: amoxicillin was the most prescribed antibiotic and less than 10% of presumed viral infections were treated. Conclusions: This "tailor-made" network set up with quality controls and external validation represents a new approach to the surveillance of pediatric infectious diseases in the digital era and could highly optimize pediatric practices. Abstract : Supplemental Digital Content is available in the text.